Improving the corrosion resistance of ZEK100 magnesium alloy by combining high-pressure torsion technology with hydroxyapatite coating. (5th November 2019) - Li, Qite; Ye, Wenbo; Gao, Hong; Gao, Lilan
Abstract: Magnesium alloys have better biocompatibility and biodegradability than conventional biomedical metal materials, but the corrosion resistance is so poor that the implant loses its mechanical integrity before the damaged tissue completely recovers. In this study, the ZEK100 magnesium alloy was pre-deformed with a high-pressure torsion (HPT) process and then fabricated hydroxyapatite (HA) coatings with different contents of Mg(OH)2 nanopowder via hydrothermal method. The specimens were characterized by scanning electron microscope (SEM) and X-ray diffraction (XRD). Meanwhile, the corrosion behavior of the specimens was evaluated by electrochemical impedance spectroscopy (EIS) and hydrogen evolution tests. Results showed that HPT processing refined the grain size and introduced a great number of twins, resulting in the enhancement of microhardness and Young's modulus of ZEK100. The abundant fine grains, twins and grain boundaries in HPT-ZEK100 can provide more nucleation sites for the HA crystal, resulting in a denser, thicker HA coating with smaller crystal sizes. In terms of the amount of Mg(OH)2 nanopowder, a 0.3 mg/mL content was most appropriate for the deposition of HA. In addition, HPT technique and surface modification by HA coating simultaneously reduced the corrosion rate of ZEK100 magnesium alloy, which virtually expands the biological application of magnesium alloys. Graphical abstract: Unlabelled Image Highlights: High-pressure torsion (HPT) enhances mechanical property of ZEK100 and increases interface bonding strength of HA coating. Addition of 0.3 mg/mL Mg(OH)2 nanopowder facilitates deposition of the densest and thickest HA coating on magnesium alloys. Both HPT and surface modification by HA coating (0.3 mg/mL Mg(OH)2 ) enhance corrosion resistance of ZEK100 significantly.